Modern problems of cattle breeding in Russia - V. I. Chinarov (Аграрная наука Евро-Северо-Востока, 2025)
The federal and regional state statistics services do not keep separate records of the number of animals in dairy and beef cattle breeding, as well as the breed structure of the livestock. However, based on official data on the volume of milk produced and productivity by category of farms in each region, the number of cows in dairy farming is determined fairly accurately by calculation. The last census of the breed composition at agricultural enterprises, conducted in 1990, recorded the uniqueness and originality of the gene pool of domestic cattle breeding. For several decades, breed transformations have been assessed based on the results of cattle breeding, which covers about 17 % of the livestock. However, due to the Russian specifics of breed accounting in breeding farms, it is necessary to conduct a breed inventory. Based on the new data, it has become possible not only to trace the evolution of breed populations, but also to obtain an objective assessment of the level of development and the state of breeding work in Russian cattle breeding. During the three years of the breed inventory, the most livestock (542.5 thousand head) were transferred to the Holstein (536.1 thousand head) and other breeds from the active part of the black-and-white population. As a result of the lack of a state policy in the field of breeding, judging by the active part of the royal stock, dairy cattle breeding in Russia is currently represented by 2/3 of the Holstein breed. The massive transition to monobred breeding and the granting of preferences to foreign producers of breeding material have become the main reasons for the deep stagnation of domestic animal husbandry. Based on a comprehensive assessment of Russian cattle breeding, proposals have been prepared to bring the industry into extended reproduction mode.